Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1002/(sici)1097-4547(19970701)49:1<107::aid-jnr12>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Multiple class I motifs revealed by sequencing naturally processed peptides eluted from rat T cell MHC molecules

Abstract: Class I major histocompatibility complex (MHC) molecules interact with a diverse array of self and foreign peptides. Displayed on the cell surface, the class I/peptide complex provides an extracellular indication of the intracellular milieu. We have characterized the Lewis rat Vbeta8.2+ T cell hybridoma C14/BW12-12A1 by FACS analysis and have used immunoaffinity chromatography to purify class I molecules from these cells. Peptides eluted from the class I molecules have been fractionated by HPLC and sequenced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Both showed a C-terminal aromatic/hydrophobic preference [20], agreeing with the C-terminal preference for TAP-B. RT1-A a , which is genetically associated with the more permissive TAP-A transporter, was found to have an arginine preference at the C terminus [15], whereas the peptide motif of RT1-A l revealed a C terminus with an aromatic/hydrophobic preference [9,21,22]. The allelic MHC class I-TAP association, as seen in rats, cannot be explained solely by the C-terminal peptide repertoire transported by the two forms of rat TAP and the specificity of the MHC class Ia/C-terminal peptide preference since, by this argument, RT1-A l would be expected to be associated with the TAP-B form of the transporter.…”
Section: Introductionmentioning
confidence: 53%
“…Both showed a C-terminal aromatic/hydrophobic preference [20], agreeing with the C-terminal preference for TAP-B. RT1-A a , which is genetically associated with the more permissive TAP-A transporter, was found to have an arginine preference at the C terminus [15], whereas the peptide motif of RT1-A l revealed a C terminus with an aromatic/hydrophobic preference [9,21,22]. The allelic MHC class I-TAP association, as seen in rats, cannot be explained solely by the C-terminal peptide repertoire transported by the two forms of rat TAP and the specificity of the MHC class Ia/C-terminal peptide preference since, by this argument, RT1-A l would be expected to be associated with the TAP-B form of the transporter.…”
Section: Introductionmentioning
confidence: 53%
“…These results further support specific interaction of 2D-CP with the TCR molecule. The A2b T-cell line used in our studies (and rat T-cells in general) expresses high levels of MHC class I molecules (45,46); indeed a comparison of the MHC class I and TCR expression has shown that TCR and MHC I molecules are expressed at similar levels by rat T-cells using the same antibodies as in the co-immunoprecipitation experiment (47). Moreover, the procedure for the immunoprecipitation of MHC class I molecules with the Ox18 antibody has been used in our laboratory to determine the binding motifs of MHC class I rat molecules.…”
Section: Resultsmentioning
confidence: 99%
“…19±20 From these eluted peptides, we identi®ed two distinct nonamer peptide motifs, including XXLXXXXXS (pattern 1) and XXYXXXXXF (pattern 2), thought to represent general patterns found in peptides that preferentially bind to two dierent RT-1B MHC class I molecules. 20 Interestingly, the BV8S2-42±50 peptide, HGLRLIHYS, contained MHC binding anchor residues identical to those found in pattern 1. Moreover, three BV8S2 peptides from the 71±95 region were identi®ed that contained anchor residues similar to those found in pattern 2.…”
Section: Recognition Of Mbp-55±69 In Eaementioning
confidence: 99%
“…Recently, we characterized both rat and mouse MHC class I bound peptides eluted from rat‐mouse hybridomas obtained by fusing Gp‐MBP‐72–89‐specific T cells with the mouse BW‐5147 fusion partner 19 , 20 . From these eluted peptides, we identified two distinct nonamer peptide motifs, including XX L XXXXX S (pattern 1) and XX Y XXXXX F (pattern 2), thought to represent general patterns found in peptides that preferentially bind to two different RT‐1B MHC class I molecules 20 . Interestingly, the BV8S2‐42–50 peptide, HG L RLIHY S , contained MHC binding anchor residues identical to those found in pattern 1.…”
Section: Recognition Of Mbp‐55–69 In Eaementioning
confidence: 99%